There’s No Sport Without Spectators – Viewing Football Games Without Spectators During the COVID-19 Pandemic - Tamir, Ilan (Frontiers in Psychology, 2022)
The presence of sports fans in the stands is considered a natural and essential element of sporting events. Beyond the atmosphere fans create and the color they add to the game, their presence reflects the idea that the game is more than a competition between two teams — it is a grand battle between communities and identities, which is also the reason that fans are willing to sacrifice so much on behalf of their team. As is other areas of life, the COVID-19 pandemic created an unusual situation, in which sporting events were held without spectators in the stadium stands. In many places around the world, professional sporting activities were permitted but spectators were not allowed into the stadiums due to social distancing restrictions. The current study examines this unique situation and through it, gains an understanding of fans’ beliefs concerning the significance of spectators and their presence in the stadium. Through in-depth interviews with football fans who regularly attend games (in the pre-pandemic period), the current study explores football fans’ experiences as they viewed “ghost games” (where teams played to empty stadiums). Findings show that this unique situation, caused by the global pandemic, heightened fans’ deep-rooted connection to sports and to their favorite team, and also exacerbated the social, emotional, and professional implications of viewing football games with no spectators.